2016
DOI: 10.1039/c6ra03210a
|View full text |Cite
|
Sign up to set email alerts
|

Use of steel slag for CO2 capture under realistic calcium-looping conditions

Abstract: aIn this study, CaO derived from steel slag pretreated with diluted acetic acid has been tested as a dry sorbent for CO 2 capture under realistic Ca-Looping (CaL) conditions, which necessarily implies calcination under high CO 2 partial pressure and fast transitions between carbonation and calcination stages. The multicycle capture performance of the sorbent has been investigated by varying the precalcination time, carbonation/calcination residence times and with the introduction of a recarbonation stage. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 65 publications
(85 reference statements)
0
31
0
Order By: Relevance
“…, steel slag annual production amounts to approximately 1 Mt in the UK alone. To use it as a CaO precursor, steel slag can be pretreated with acetic acid to obtain calcium acetate [Ca(CH3COO) 2 ] . Results from TGA tests show that the decomposition of calcium acetate occurs mainly in three steps: i) an initial dehydration, which occurs from ambient temperature to approximately 250 °C; ii) calcium acetate decomposition between 300 and 450 °C to release acetone and CaCO 3 , and iii) calcination of CaCO 3 in the range from 620 to 700 °C.…”
Section: Multicycle Co2 Capture Behavior Of Limestone Dolomite and Smentioning
confidence: 99%
See 3 more Smart Citations
“…, steel slag annual production amounts to approximately 1 Mt in the UK alone. To use it as a CaO precursor, steel slag can be pretreated with acetic acid to obtain calcium acetate [Ca(CH3COO) 2 ] . Results from TGA tests show that the decomposition of calcium acetate occurs mainly in three steps: i) an initial dehydration, which occurs from ambient temperature to approximately 250 °C; ii) calcium acetate decomposition between 300 and 450 °C to release acetone and CaCO 3 , and iii) calcination of CaCO 3 in the range from 620 to 700 °C.…”
Section: Multicycle Co2 Capture Behavior Of Limestone Dolomite and Smentioning
confidence: 99%
“…To use it as a CaO precursor, steel slag can be pretreated with acetic acid to obtain calcium acetate [Ca(CH3COO) 2 ] . Results from TGA tests show that the decomposition of calcium acetate occurs mainly in three steps: i) an initial dehydration, which occurs from ambient temperature to approximately 250 °C; ii) calcium acetate decomposition between 300 and 450 °C to release acetone and CaCO 3 , and iii) calcination of CaCO 3 in the range from 620 to 700 °C. According to TGA results, the CaO‐based sorbent derived from steel slag presents a low deactivation rate at realistic CaL conditions, which would expectedly improve the CO 2 capture efficiency of the process.…”
Section: Multicycle Co2 Capture Behavior Of Limestone Dolomite and Smentioning
confidence: 99%
See 2 more Smart Citations
“…By this study, BFS treated by AR was confirmed to be useful for CO 2 mineralization in terms of producing high-purity CaCO 3 for industrially useful materials as fillers for paper making and for capturing CO 2 materials via the Ca-looping cycle [37]. Amorphous silica powder can be used for preparing semiconductors, as well as an adsorbent for various potential applications [29], e.g., dehumidification and elimination of toxic matter.…”
Section: Discussionmentioning
confidence: 99%